Whole body coordination patterning in volleyball spikes under various task constraints: exploratory cluster analysis based on self-organising maps - Sarvestan, J.; Svoboda, Z.; Baeyens, J.-P.; Serrien, B. (Sports Biomechanics, 2023)
Task and environment-related constraints can influence spike performance in volleyball players. This study was designated to investigate the impact of awareness of the presence or absence of a defensive block by the opponents on the performance and coordination pattern of spikes in elite volleyball attackers. Simulating a real-game scenario, 10 elite youth attackers (aged 15.5 ± 0.7 years) executed six spikes each with prior notification about the presence/absence of defences and six spikes without any notification. In each condition, they were blocked by two opponents in three trials. The coordination patterning of the attackers was explored using cluster analysis based on a Self-Organising Map (SOM). The SOMs and the cluster analysis showed that the coordination pattern of the spike execution was very individual-specific; however, in the third layer of the cluster analysis, it was revealed that the movement pattern of spike execution had similarities in the scenario wherein the players had prior awareness of the defences. Providing the attackers with information on the opponents` condition or performance could shift the attackers` focus from a game-oriented condition to the rivals` behaviour, which consequently resulted in deterioration of their spike performance.